Heavy-flavor hadron decays producing muon cross sections in pp collisions at high transverse momentum - Zhang, Zuman; Li, Sha; Yu, Ning; Zhu, Zhong (Frontiers in Physics, 2023)
The focus of this work will be on investigating and comparing two methods for calculating the cross sections of muons produced by the decay of heavy-flavour hadrons in pp collisions cover the interval 2< p_T< 20 GeV/c at a center-of-mass energy of s = 7 TeV. One method involves using the Fixed-Order plus Next-to-Leading Logarithms (FONLL) approach to scale the measured p_T-differential cross section of muons from heavy-flavour hadron decay in pp collisions at a center-of-mass energy of s = 5.02 TeV. The other method involves using FONLL calculations to extrapolate the published measured p_T-differential cross section at s = 7 TeV to higher p_T. In these two methods we can use the published measured p_T-differential cross section at s = 5.02 TeV and s = 7 TeV cover the interval 2< p_T< 20 GeV/c and 2< p_T< 12 GeV/c respectively. In terms of consistency within uncertainties, the results from both methods will be compared not only to pQCD-based FONLL calculations, but also to each other. Because they provide the necessary pp reference, these calculations are critical for determining the nuclear modification factor of muons from heavy flavour decays in heavy-ion collisions.